Cesarean section induced dysbiosis promotes type 2 immunity but not oxazolone-induced dermatitis in mice - Line Fisker Zachariassen; Maria Bernadette Bergh Ebert; Caroline Märta Junker Mentzel; Ling Deng; Lukasz Krych; Dennis Sandris Nielsen; Jakob Stokholm; Camilla Hartmann Friis Hansen (Gut Microbes, 2023)
ABSTRACTDelivery by cesarean section (CS) is associated with an altered gut microbiota (GM) colonization and a higher risk of later chronic inflammatory diseases. Studies investigating the association between CS and atopic dermatitis (AD) are contradictive and often biased by confounding factors. The aim of this study was therefore to provide experimental evidence for the association between CS and AD in a mouse model and clarify the role of the GM changes associated with CS. It was hypothesized that CS-delivered mice, and human CS-GM transplanted mice develop severe dermatitis due to early dysbiosis. BALB/c mice delivered by CS or vaginally (VD) as well as BALB/c mice transplanted with GM from CS or VD human donors were challenged with oxazolone on the ear. The severity of dermatitis was evaluated by ear thickness and clinical and histopathological assessment which were similar between all groups. The immune response was assessed by serum IgE concentration, local cytokine response, and presence of immune cells in the draining lymph node. Both CS-delivered mice and mice inoculated with human CS-GM had a higher IgE concentration. A higher proportion of Th2 cells were also found in the CS-GM inoculated mice, but no differences were seen in the cytokine levels in the affected ears. In support of the experimental findings, a human cohort analysis from where the GM samples were obtained found that delivery mode did not affect the children’s risk of developing AD. In conclusion, CS-GM enhanced a Th2 biased immune response, but had no effect on oxazolone-induced dermatitis in mice.